Outlier Removal Technique for Estimating Link Travel Times Using DSRC Probes - Jang, Jinhwan (IJRDO -Journal of Computer Science Engineering, 2017)
Abstract- As electronic toll collection systems based on 5.8 GHz dedicated short-range communications (DSRC) have become popular, real-life travel time collection via DSRC systems is attracting more interest. The DSRC system, composed of an on-board unit and a roadside unit, has the advantage of gathering section travel times directly. However, outliers resulting from vehicles entering or exiting a section, parking activities, and so on have been considered a critical hurdle to be overcome in estimating reliable travel times. In this study, a modified Ferguson test is applied to clean DSRC probe data on a signalized rural highway in Korea. The proposed method was tested with 24-h block real-world data, indicating satisfactory results